Pandangan Sikap Intovert dalam Filsafat Stoikisme - Muhammad Fazril Ubaidillah (Gunung Djati Conference Series, 2023)
This study aims to discuss introverted attitudes in the view of stoicism philosophy. This study uses a qualitative approach by applying the method of library research (library research). The formal object of this study is the stoicism of Marcus Aurelius, while the material object is introverted behavior. The results and discussion in this study indicate that Marcus Aurelius' stoicism philosophy emphasizes that humans must "live in harmony with nature" which prioritizes reason and rationality. Introversion is a character or trait that is closed, shy, always cornered, looks less sociable so tends to be alone. Someone who tends to have an introverted attitude mostly prefers not to be too exposed in their social environment, because some of them have problems in terms of self-confidence. This study concludes, there are several theories of Marcus Aurelius that are compatible with introverted attitudes, starting with self-control, focusing on goals that we can achieve, and contemplating all circumstances in solitude.